Breast Cancer Survivors’ Lived Experience of Adjuvant Hormone Therapy: A Thematic Analysis of Medication Side Effects and Their Impact on Adherence - Ibrar, Maryam; Peddie, Nicola; Agnew, Sommer; Diserholt, Amanda; Fleming, Leanne (Frontiers in Psychology, 2022)
Objectives: Side effects from Hormone Therapy (HT) impact medication adherence in breast cancer survivors. Understanding the most distressing HT side effects and their impacts, may inform the development and implementation of interventions to alleviate these side effects and maximize HT adherence. This study aimed to explore the lived experience of adjuvant HT and understand the impact of HT side effects on adherence in a sample of breast cancer survivors. Methods: Twenty-five female breast cancer survivors who were currently taking adjuvant HT participated in the study. One-to-one, online, semi-structured interviews were conducted to explore (i) specific side effects from HT and (ii) the impact of these side effects on HT adherence. Data were analysed using the Clarke and Braun (2006) approach to Thematic Analysis. Results: The most commonly reported side effects were sleep disturbance, hot flashes, anxiety and joint pain. Data exploring the impacts of these side effects on HT adherence were thematically synthesised into four analytical themes: “A bitter pill to swallow”, “Seeking relief”, “Taking control” and “The only way out is through”. These themes encompass 14 sub-themes that encapsulate participants’ daily struggle with HT side effects and the coping strategies developed to manage these. Conclusions: Adverse side effects from HT, such as sleep disturbance, hot flashes, pain and anxiety, impair quality of life and increase the likelihood of participants’ becoming non-adherent to HT medication. In order to maximize HT adherence and reduce breast cancer mortality, HT side effects should be closely monitored to identify individuals who would benefit from targeted intervention strategies, aimed at alleviating these side effects.